Dinamika masyarakat dalam moderasi beragama di ‎Indonesia - Aldakhil, Muhammad Rizqy; Azmi, Muhammad Ulul (Maliki Interdisciplinary Journal, 2023)
Religious moderation is an approach that aims to balance religion and practical action in everyday life through several methods. It is a deep understanding of religious principles and adaptation to modern contexts that aims to promote tolerance, interfaith co-operation and avoid extremism. This concept is essential for maintaining social stability, promoting harmony, and respecting religious freedom in a multicultural society.